Hypomethylation of the Soluble Fms-like Tyrosine Kinase 1 (sFlt-1) Gene Promoter Region and Elevated sFlt-1 Placental Expression as Risk Factors for Preeclampsia - Anak Agung Ngurah Jaya Kusuma; I Made Darmayasa; I Gede Mega Putra; Anom Suardika; Evert Solomon Pangkahila; Vidya Saraswati Putri Duarsa; William William (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Preeclampsia significantly contributes to maternal and fetal morbidity and mortality worldwide, marked by an imbalance of angiogenic factors, particularly increased soluble Fms-like tyrosine kinase-1 (sFlt-1), leading to endothelial dysfunction. Epigenetic regulation, including DNA methylation of the sFlt-1 promoter, has been suggested to influence sFlt-1 expression, but the data in Indonesian population are limited. This study was perfmed to determine whether hypomethylation of the sFlt-1 promoter and elevated placental sFlt-1 expression are associated with increased risk of preeclampsia.METHODS: A case-control study was conducted involving 30 women with preeclampsia and 30 normotensive pregnant women. Subjects were selected based on eligibility criteria that included singleton pregnancy and gestational age of ≥37 weeks. DNA methylation of the sFlt-1 promoter was assessed using methylation-specific polymerase chain reaction (PCR), and sFlt-1 expression was measured by enzyme-linked immunosorbent assay (ELISA). Statistical analyses, including Mann-Whitney U, Chi-square tests, Receiver-operating characteristic (ROC) curve analysis, and multivariate logistic regression, were performed to evaluate the relationship between methylation levels, gene expression, and preeclampsia risk.RESULTS: The preeclampsia group had significantly lower methylation levels of sFlt-1 promoter and higher placental sFlt-1 expression (both p<0.001). Hypomethylation of sFlt-1 promoter (adjusted odd ratio (AOR): 21.18; 95% CI: 2.49–179.72; p=0.005), high sFlt-1 expression (AOR: 12.55; 95% CI: 1.95–80.83; p=0.008), and obesity (AOR: 11.15; 95% CI: 2.01–61.78; p=0.006) were identified as independent risk factors for preeclampsia.CONCLUSION: Hypomethylation of sFlt-1 promoter and elevated placental sFlt-1 expression are significant independent risk factors for preeclampsia. These findings suggest that hypomethylation of sFlt-1 promoter and elevated placental sFlt-1 expression may serve as potential epigenetic biomarkers for early detection and targeted intervention in preeclampsia.KEYWORDS: preeclampsia, sFlt-1, gene expression, hypomethylation, placenta, risk factor